Chalcolithic stamp seals from Tepe Gheshlagh, and a look into their application in ownership and exchange systems - Mahnaz Sharifi; Abbas Motarjem (Documenta Praehistorica)
Tepe Gheshlagh is one of the major sites with deposits of the Chalcolithic period in the east of the Central Zagros. The central question in the present study was the administrative system and ownership in the Chalcolithic period. With a descriptive-analytical method, an attempt was made to expound on Gheshlagh’s glyptic assemblage that attest to the existence of an ownership system and commercial exchanges. A structural analysis of the glyptic iconography suggested that each of the linear, circular, or repeating patterns were less mere personal insignias intended to exclude the possibility of alteration or forgery than they were marks belonging to a pre-literate system where each sign/symbol stood for individual commodity types that were transported or exchanged as such. At the same time, the composition of these widely varying geometric motifs followed certain conventions.